2002
DOI: 10.1093/glycob/12.5.299
|View full text |Cite
|
Sign up to set email alerts
|

The presence of Lewis a epitopes in Arabidopsis thaliana glycoconjugates depends on an active  4-fucosyltransferase gene

Abstract: The presence of an alpha4-fucosyltransferase in plants was first deduced from the characterization of Lewis-a glycoepitopes in some N-glycans. The first plant gene encoding an alpha4-fucosyltransferase was recently cloned in Beta vulgaris. In the present paper we provide evidence for the presence of an alpha4-fucosyltransferase in A. thaliana by measurement of this glycosyltransferase activity from a purified microsomal preparation and by immunolocalization of Le(a) epitopes on glycans N-linked to glycoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 28 publications
5
59
0
Order By: Relevance
“…The presence of virtually exclusive and fully processed galactosylated structures on mAbs derived from GalT ϩ plants indicates that the rat-derived ST-CTS region contains an extremely efficient trans-Golgi targeting domain in plants. However, other CTS domains of plant glycosylation enzymes that act in the final stage of the pathway like ␤1,3-GalT or ␣1,4-fucosyltransferase might be similarly effective (23,24). Our results emphasize the importance of sub-Golgi localization of glycosylation enzymes to obtain proper glycosylation and indicate that spatial distribution is a driving force that directs N-glycan processing within the plant Golgi.…”
Section: Discussionmentioning
confidence: 64%
“…The presence of virtually exclusive and fully processed galactosylated structures on mAbs derived from GalT ϩ plants indicates that the rat-derived ST-CTS region contains an extremely efficient trans-Golgi targeting domain in plants. However, other CTS domains of plant glycosylation enzymes that act in the final stage of the pathway like ␤1,3-GalT or ␣1,4-fucosyltransferase might be similarly effective (23,24). Our results emphasize the importance of sub-Golgi localization of glycosylation enzymes to obtain proper glycosylation and indicate that spatial distribution is a driving force that directs N-glycan processing within the plant Golgi.…”
Section: Discussionmentioning
confidence: 64%
“…However, in a later study, the epitope was detected in Arabidopsis seedlings by immunoblots using Le a -specific antibodies (Lé onard et al, 2002). To address these conflicting results, we performed a systematic analysis of N-glycans present in different organs of Arabidopsis.…”
Section: Expression Of Le a Epitopes In Arabidopsismentioning
confidence: 99%
“…Le a structures were found primarily on soluble and membrane-bound extracellular proteins and were reported as absent from vacuolar proteins (Fitchette-Lainé et al, 1997;Melo et al, 1997;Fitchette et al, 1999). Although Le a structures are otherwise widespread in the plant kingdom, most studies have failed to detect Le a containing N-glycans in Arabidopsis thaliana and other Brassicaceae (e.g., Fitchette-Lainé et al, 1997;Wilson et al, 2001b), with two exceptions where Le a epitopes were detected by immunological means in Arabidopsis root tips and seedlings, respectively (Jin et al, 2001;Lé onard et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, using antibodies against the main glycoepitopes present in plant N-glycans we have shown that b1,2-xylose is added mainly in the medial Golgi cisternae, a1,3-fucosylation occurs mostly in the trans Golgi (Fitchette et al 1994), while the plant Lewis a antennae biosynthesis is a late Golgi event occurring in the trans Golgi and trans Golgi network (TGN) (Fitchette et al, 1999). Besides those indirect approaches, the recent cloning of several glycosyltransferases from plants (Leiter et al, 1999;Strasser et al, 1999Strasser et al, , 2000Faik et al, 2000;Bakker et al, 2001;Wilson et al, 2001;Faik et al, 2002;Leonard et al, 2002) and the identification of about 250 putative plant glycosyltransferases in Arabidopsis thaliana genome (Henrissat et al, 2001) has paved the way for a detailed characterization of plant glycosyltransferases. This was illustrated in a recent paper providing preliminary indications on the signal responsible for localization of N-acetylglucosaminyltransferase I in the Golgi apparatus of tobacco cells (Essl et al, 1999).…”
Section: Introductionmentioning
confidence: 99%